2022
DOI: 10.3390/ijms231911342
|View full text |Cite
|
Sign up to set email alerts
|

Motor Behavioral Deficits in the Cuprizone Model: Validity of the Rotarod Test Paradigm

Abstract: Multiple Sclerosis (MS) is a neuroinflammatory disorder, which is histopathologically characterized by multifocal inflammatory demyelinating lesions affecting both the central nervous system’s white and grey matter. Especially during the progressive phases of the disease, immunomodulatory treatment strategies lose their effectiveness. To develop novel progressive MS treatment options, pre-clinical animal models are indispensable. Among the various different models, the cuprizone de- and remyelination model is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 118 publications
2
12
0
1
Order By: Relevance
“…The pronounced, persistent cellular deficits following acute and chronic cuprizone treatment led us to investigate whether they were accompanied by functional deficits in vivo . Most studies assessing behavioral deficits after cuprizone exposure have focused on the acute demyelination paradigm and motor function deficits and/or psychiatric effects such as social and anxiogenic behaviors ( Sen et al, 2019 ; Lubrich et al, 2022 ). Using a complex wheel running test, Hibbits et al (2009) showed impaired bilateral sensorimotor coordination in cuprizone-treated mice and function recovery upon remyelination following acute demyelination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pronounced, persistent cellular deficits following acute and chronic cuprizone treatment led us to investigate whether they were accompanied by functional deficits in vivo . Most studies assessing behavioral deficits after cuprizone exposure have focused on the acute demyelination paradigm and motor function deficits and/or psychiatric effects such as social and anxiogenic behaviors ( Sen et al, 2019 ; Lubrich et al, 2022 ). Using a complex wheel running test, Hibbits et al (2009) showed impaired bilateral sensorimotor coordination in cuprizone-treated mice and function recovery upon remyelination following acute demyelination.…”
Section: Resultsmentioning
confidence: 99%
“…The functional outcome of cuprizone-induced CNS de/remyelination, particularly motor functional impairments, has been examined in multiple studies ( Lubrich et al, 2022 ). However, it is still unclear to what extent functional impairments recover upon remyelination, particularly in the context of chronic de/remyelination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rotarod test, first proposed by Dunham and Miya, is used to assess motor coordination and balance abilities 35 . It has been widely used in assessing motor functions in cases of intracranial hemorrhage, multiple sclerosis, and traumatic brain injury [36][37][38] .Referring to the previous experimental protocols 39 , before the official test begins, let the mice undergo adaptive training on the rotating rod at a constant speed of 15 rpm for 15 minutes. During this period, if a mouse falls off, it will be put back on the rotating rod to continue training until it can walk steadily on it.…”
Section: Rotarod Testmentioning
confidence: 99%
“…The duration for when the mouse remained on and endured the rotarod and the rotating speed at which the mouse first fell were recorded. Usually, mice can maintain their balance unlimitedly (Lubrich et al, 2022).…”
Section: Rotarod Testmentioning
confidence: 99%